Double-Quantum-Well AlGaN/GaN Field Effect Transistors with Top and Back Gates: Electrical and Noise Characteristics - Maksym Dub (Micromachines, 2021)
AlGaN/GaN fin-shaped and large-area grating gate transistors with two layers of two-dimensional electron gas and a back gate were fabricated and studied experimentally. The back gate allowed reducing the subthreshold leakage current, improving the subthreshold slope and adjusting the threshold voltage. At a certain back gate voltage, transistors operated as normally-off devices. Grating gate transistors with a high gate area demonstrated little subthreshold leakage current, which could be further reduced by the back gate. The low frequency noise measurements indicated identical noise properties and the same trap density responsible for noise when the transistors were controlled by either top or back gates. This result was explained by the tunneling of electrons to the traps in AlGaN as the main noise mechanism. The trap density extracted from the noise measurements was similar or less than that reported in the majority of publications on regular AlGaN/GaN transistors.